Terpenoids from the whole plants of Saussurea medusa maxim. And their chemotaxonomic significance. (December 2022) - Cao, Jing-Ya; Mei, Li-Juan; Wu, Nan; Yu, Rui-Tao; Tao, Yan-Duo
Abstract: Phytochemical investigation of the whole plants of Saussurea medusa Maxim. (Compositae) led to the isolation and characterization of fourteen terpenoids, including ten megastigmane sesquiterpenoids (1 –10 ) and four monoterpenoids (11 –14 ). Their structures were identified by spectroscopic analyses and comparing with literature data. In this research, compounds 1 –6, 11 and 12 were firstly obtained from the Compositae family. Additionally, compounds 7, 8 and 13 were mentioned from S. medusa for the first time. In this paper chemotaxonomic significance of these compounds was discussed. Graphical abstract: Terpenoids from the whole plants of Saussurea medusa Maxim. Image 1 Highlights: Compounds 1 –6, 11 and 12 were firstly obtained from the Compositae family. Compounds 7, 8 and 13 were mentioned from S. medusa for the first time. Chemotaxonomic significance of these compounds was discussed.